SUPPORT FOR THE PROCESS OF SOCIAL ADAPTATION OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS - Marzec, Danuta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The most recent tendencies in teaching children with developmental deficits advocate using inclusive educations which allow for an optimization of the process of social adaptation. Rehabilitation programs to support these children are an integral part of individual educational programs which are developed for each student and based on the positive diagnosis that accentuates child's strengths. The process of social adaptation of a child with disability starts in families and is continued in nursery schools and schools. Lessons at schools and extra-curricular classes open up opportunities for starting interpersonal contacts that play a fundamental role in the process of social adaptation. The particular importance can be from physical activity and various forms of physical recreation. The support for the development and process of social adaptation through various forms of physical activity results from the natural needs of a child. The questionnaire survey conducted among parents and teachers demonstrated that the respondents realize the importance of physical activity in the process of social development of children with developmental dysfunctions.